New considerations on hypertensive disorders of pregnancy The burden of non-communicable diseases in postmenopausal women - Pacheco-Romero, José (2018)
New reports consider that approximately 30000 deaths are annually attributed to hypertensive disorders including preeclampsia, eclampsia, and HELLP syndrome(1,2). In the United States, hypertension-related disorders account for approximately 7,4% of the almost 800 pregnancy-related deaths that occur each year, which shows an important decline of this rate from 17.6% in 1990(3). In Peru, the rate is about 32%(4). Women with preeclampsia/eclampsia have about 3 to 25 times a higher risk of severe pregnancy complications including placental abruption, disseminated intravascular coagulation, renal failure, pulmonary edema and aspiration pneumonia(5,6).